Educational Services for Intellectual Capital Growth or Transmission of Culture for Transfer of Knowledge-Consumer Satisfaction at St. Petersburg Universities - Nadezhda N. Pokrovskaia; Marianna Yu. Ababkova; Denis A. Fedorov (MDPI AG, 2019)
Higher education has complex roles in society, the economy, and politics; it helps to transmit culture, transfer knowledge, and develop the personality of citizens. This diversity of roles is confronted with the limited resources that are related to the sources of financing, that is, students and their families, the national government, and local authorities, among others. The discussions related to the role of universities concern the economy of knowledge and the digital tools influencing education. The specific case of St. Petersburg universities simultaneously represents the impact of the deep socio-political transition from Soviet society to the liberal principles of a market economy, including the perception of higher education institutions as service sector companies. The services allowed by universities include research and training; however, from the consumer point of view, universities should create specific value: the increase of the intellectual components of human capital. These complex functions are interconnected. During 2017−2018, a survey in St. Petersburg was organised to ascertain the opinion of students, professors, and employers on the quality of education. The results of the survey demonstrate the impact of the exaggerated implementation of the liberal principles on education, both positive and negative. The positive effect is the renewing of content and innovative training techniques due to competition among universities. The negative impacts include the preference for popular disciplines and the opportunistic behavior of students that lose their passion for acquiring knowledge and choose instead the passive attitude of consumers of a competitive service. They are less interested in the sphere of their studies, in searching for a job, in the interaction with other social and economic actors, and even in the research and education options presented by the universities.